Tobacco Regulation, Economics, and Public Health, Volume II Clearing the Air on E-Cigarettes and Harm Reduction - Hampsher-Monk, Samuel C.; Prieger, James E.; Patwardhan, Sudhanshu (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
XXII, 306 p. 13 illus., 12 illus. in color.